2021
DOI: 10.3390/electronics10232992
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Intentions to Use Distance Education Platforms: An Investigation into Expanding the Technology Acceptance Model through Social Cognitive Theory

Abstract: The current study aims to investigate the crucial factors that influence the behavioral intentions of students to use distance education platforms (DEPs). The tested Davis Expanded Technology Acceptance Model (TAM) was applied with Bandura’s social cognitive theory (SCT). This study included 453 university students using DEPs in the Kingdom of Saudi Arabia. A quantitative approach was adopted, and the results revealed that both perceived ease of use and usefulness have a strong influence on student intentions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
(120 reference statements)
2
15
0
Order By: Relevance
“…However, many studies related to the field of ICT (Al-Dokhny et al, 2021 ; Al-Rahmi et al, 2019 ; Alyoussef, 2021 ; Tarasov et al, 2020 ) were conducted in light of the technology acceptance model (TAM) developed by Davis ( 1989 ), which confirmed that providing an effective e-learning environment for students helps increase their behavioral intention to use it in the future. The environment must provide perceived ease of use, and perceived usefulness, where the perceived ease of use makes easy access to the resources of these systems through the hand-easy tools, which in turn affect their perceived usefulness.…”
Section: Discussionmentioning
confidence: 95%
“…However, many studies related to the field of ICT (Al-Dokhny et al, 2021 ; Al-Rahmi et al, 2019 ; Alyoussef, 2021 ; Tarasov et al, 2020 ) were conducted in light of the technology acceptance model (TAM) developed by Davis ( 1989 ), which confirmed that providing an effective e-learning environment for students helps increase their behavioral intention to use it in the future. The environment must provide perceived ease of use, and perceived usefulness, where the perceived ease of use makes easy access to the resources of these systems through the hand-easy tools, which in turn affect their perceived usefulness.…”
Section: Discussionmentioning
confidence: 95%
“…However, there are still areas where our students' consistent use of elearning could be improved. The key elements of the e-learning model developed by [5], [9] and [10] to strengthen the ongoing intention to utilize the e-learning system in education.…”
Section: E-learning In Higher Education Institutionmentioning
confidence: 99%
“…The Gulf Cooperation Council (GCC) has embraced and accepted the e-learning system in many GCC nations. The Middle East's educational transformation is being led by Arab Gulf areas [9].…”
Section: E-learning In Higher Education Institutionmentioning
confidence: 99%
See 2 more Smart Citations